How does digital governance affect the level of domestic waste separation for rural residents? Empirical evidence from rural areas in Jiangsu Province, China - Chen, Xi; Xing, Lirong; Wang, Kai; Lu, Jianzhen (Frontiers in Public Health, 2023)
The management of rural domestic waste is directly related to the quality of China’s rural habitat and the ecological security of the countryside, and is one of the important tasks of rural revitalization. Based on the perspective of digital technology empowering rural governance, this study uses the China Land Economic Survey (CLES) data to empirically test the impact of digital governance on the level of domestic waste separation for rural residents by constructing the ordered probit model. The results show that in the process of rural governance modernization, digital governance helps to improve the level of domestic waste separation for rural residents in the process of rural governance modernization, and the findings still hold after robustness tests. Mechanistic tests showed that digital governance can impact the level of domestic waste separation for rural residents through cadre-mass relationship and institutional trust. The findings of this study provide a new perspective on good environmental governance in China’s countryside and have important implications for promoting the improvement of rural habitat quality.